Cross Sectional Study on Knowledge and Attitude among Women in The Reproductive Age Group Towards Sex Ratio and PC& PNDT Act in Urban Field Practice Areas of Medical College, Bengaluru - Lovely S Livingston; Maheswaran R; Shruthi Shetty M; Menta Sai Rikesh; Daniel Ernest (Medsci Publications, 2019)
Introduction: Preference for a son still continues to be prevalent in modern India. In 1994, the government of India passed the Prenatal Diagnostic Techniques Act with the aim of preventing female feticide. Objectives: To assess the knowledge and attitude of reproductive age group women towards sex determination and PC & PNDT Act in the Urban Field Practice Areas of a medical college. Methodology: Cross sectional study was carried out from March-April 2018 in Urban Health Centers of a medical college in Bengaluru. Women above 18 years of age, visiting the Urban Health Centers after taking informed consent were included in the study. Considering the study by Deshpande SR et al, the proportion of women having knowledge of 32.49%, the sample size was 212. A Questionnaire was made for this study based on similar studies with sections on knowledge & attitude of women towards sex ratio and PC & PNDT ACT. Descriptive statistics and Chi-square was calculated using SPSS. Results: Around 71.4% were not aware of the decline in sex ratio. 79.1% were not aware of PC and PNDT Act. Around 49.1% did not know who can be punished under the act. Educated women and those belonging to a higher socio-economic status were aware about PC & PNDT Act and decline in sex ratio. Conclusion: Educating the community will prevent the decline in sex ratio and female feticide through PC& PNDT Act.